Alienation from nature and the role of forgotten tradition in Keris Mas' Jungle of Hope and K. S. Maniam's Between Lives - Zainal, Zainor Izat (Universiti Putra Malaysia Press, 2014)
This essay looks at Keris Mas’ Jungle of Hope (1984) and K.S. Maniam’s Between Lives (2003) and discusses how humanity’s alienation from nature gets different treatments by these two prominent Malaysian writers. This estrangement resonates with current environmentalism as it is seen as complicit in conditioning humanity’s thinking that they are not a part of nature, causing them to take the anthropocentric and utilitarian attitudes that contribute further to environmental woes. Alienation from nature is to a large extent, the reflection of the environmental conditions in which the writers find themselves and the different phases in the country’s environmental history, in which the texts are placed. Keris through Jungle of Hope delves into the onset of this alienation, focusing on the trauma felt by Malay peasants, caught between environmental realities and tradition. Maniam through Between Lives also delves into this rift. He, however, offers a way to heal this rupture – by going back to cultural and religious tradition. Indeed, forgotten tradition is reclaimed and revived in both texts but Maniam seems to foreground forgotten tradition as a way to heal this estrangement from nature. Both texts nevertheless, serve as valuable resources for thinking about alienation and its effects on humanity; and the immense capacity that humanity has to amend their relationship with nature.